The responsibility to protect and the right of veto in the Security Council: some recent examples (Journal of the Spanish Institute for Strategic Studies, 2018)
As currently conceived, and to ensure its better practical application, the concept of the Responsibility to Protect requires a reform of the right of veto. The French proposal dating from 2013 on this subject warrants in-depth consideration. In any case, the responsibility to protect remains in effect, as proven by UN Security Council Resolution 2127 (2013), adopted as a response to the conflict in the Central African Republic.